Projeto e especificação de uma máquina de ensaio de fadiga por flexao rotativa - Melo, Paulo Roberto (Universidade Federal Rural do Semi-Árido, 2017)
This work has the objective of specifying and designing in a detailed way a machine for the realization of the fatigue test by rotary bending. It was used as basis, norms, books and works found in the literature related to the subject, as well as the knowledge acquired during the course of mechanical engineering and the aid of software to carry out the project. According to Oliveira (2004), we can define the project methodology as a collection of documents and tools to support the project process, whose main purpose is to help designers to make the best decisions to solve specific problems. Thus, at the end of the project study, it was possible to compare the results obtained with the results found in the literature, combining safety and better design optimization.
Monografia
Keywords: Projeto de máquinas; Elementos de máquinas; Fadiga; Ensaio mecânico; Design of machines; Elements of machines; Fatigue; Mechanical testing; ENGENHARIAS::ENGENHARIA MECANICA